The use of angiotensin II receptor blocker is associated with greater recovery of cardiac function than angiotensin‐converting enzyme inhibitor in dilated cardiomyopathy. (8th February 2022) - Enzan, Nobuyuki; Matsushima, Shouji; Ide, Tomomi; Tohyama, Takeshi; Funakoshi, Kouta; Higo, Taiki; Tsutsui, Hiroyuki
Abstract: Aims: Angiotensin‐converting enzyme inhibitors (ACEis) or angiotensin II receptor blockers (ARBs) have been shown to be associated with recovery of cardiac function in patients with dilated cardiomyopathy (DCM). The aim of this study was to assess comparative effectiveness of ACEis vs. ARBs on recovery of left ventricular ejection fraction (LVEF) among patients with DCM. Methods and results: We analysed the clinical personal records of DCM, a national database of the Japanese Ministry of Health, Labour and Welfare, from 2003 to 2014. Patients with LVEF < 40% and on either ACEis or ARBs were included. Eligible patients were divided into two groups according to the use of ACEis or ARBs. A one‐to‐one propensity case‐matched analysis was used. The primary outcome was defined as LVEF ≥ 40% at 3 years of follow‐up. Out of 4618 eligible patients, 2238 patients received ACEis and 2380 patients received ARBs. Propensity score matching yielded 1341 pairs. Mean age was 56.0 years, 2041 (76.1%) were male, median duration of heart failure was 1 year, and mean LVEF was 27.6%. The primary outcome was observed more frequently in ARB group than in ACEi group (59.8% vs. 54.1%; odds ratio 1.26; 95% confidence interval 1.08–1.47; P = 0.003). The per‐protocol analysis showed similar results (62.0% vs. 54.0%; odds ratio 1.39; 95% confidence interval 1.17–1.66; P < 0.001). The change in LVEF from baseline to 3 years of follow‐up was greater in ARB group than in ACEi group (15.8 ± 0.4% vs. 14.0 ± 0.4%, P = 0.003). The subgroup analysis showed that this effect was observed independently of systolic blood pressure, heart rate, LVEF, chronic kidney disease, and concomitant use of beta‐blockers and mineralocorticoid receptor antagonists. Conclusions: The use of ARBs was associated with LVEF recovery more frequently than ACEis among patients with DCM and reduced LVEF.